2017
DOI: 10.1177/2042018817708910
|View full text |Cite
|
Sign up to set email alerts
|

Expression of JAZF1, ABCC8, KCNJ11and Notch2 genes and vitamin D receptor polymorphisms in type 2 diabetes, and their association with microvascular complications

Abstract: Background:We studied JAZF1, ABCC8, KCNJ11and Notch2 gene expression and vitamin D receptor (VDR) polymorphisms (Fok1 and Bsm1) in patients with type 2 diabetes mellitus (T2DM) and tried to find out their association with microvascular complications in these patients. Methods: The study was conducted on 180 patients (93 complicated and 87 noncomplicated) and 150 healthy subjects. Reverse-transcriptase polymerase chain reaction (RT-PCR) was used to assess gene expression and real-time PCR was used to detect VDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…including migraine, sickle cell disease, Behcet's disease, and branch retinal artery occlusion (66)(67)(68)(69)(70)(71). Among the identified genes in this study, several genes including MTHFR, NOS3, SLC44A2, and NOTCH2 are associated with prothrombotic risk factors and various vascular disorders (72)(73)(74)(75). The MTHFR encodes methylenetetrahydrofolate reductase which catalyzes the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate, a co-substrate for homocystein remethylation to methionine (29).…”
Section: Discussionmentioning
confidence: 96%
“…including migraine, sickle cell disease, Behcet's disease, and branch retinal artery occlusion (66)(67)(68)(69)(70)(71). Among the identified genes in this study, several genes including MTHFR, NOS3, SLC44A2, and NOTCH2 are associated with prothrombotic risk factors and various vascular disorders (72)(73)(74)(75). The MTHFR encodes methylenetetrahydrofolate reductase which catalyzes the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate, a co-substrate for homocystein remethylation to methionine (29).…”
Section: Discussionmentioning
confidence: 96%
“…This gene is highly expressed in adipose and liver tissues, which can affect the regulation of gluconeogenesis, insulin sensitivity, lipid metabolism, and inflammatory reactions [ 8 ]. There is also a correlation between JAZF1 polymorphisms and the development of T2D [ 9 ]. However, the mechanism underlying this relationship is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Studies have shown that vitamin D can reduce inflammation and autoimmune response, promote insulin synthesis and secretion, and play a regulatory role in the occurrence and development of diabetes and its complications. [ 4 ] Vitamin D deficiency has been shown to be an important risk factor for limited secretion of islet β cells and insulin resistance. [ 5 ] Based on the analysis of relevant data from 110 countries, The International Diabetes Federation predicts that the number of global diabetes patients will reach 592 million in 2035.…”
Section: Introductionmentioning
confidence: 99%